The Flypaper Effect on Regional Original Revenue, General Allocation Fund, and Special Allocation Fund Toward Regional Expenditure in Sorong Regency - Kambuaya, Anzek Mey; Sani, Sri Rosmiati; Shifa, Mutiara; Ansari, Leli Putri; Hartini, Hartini (Universitas Syiah Kuala, 2025)
This study examines the presence of the flypaper effect on regional government spending in Sorong Regency over the period 20132023. Using multiple linear regression, the analysis includes three independent variables: Regional Original Revenue (ROR), General Allocation Fund (GAF), and Special Allocation Fund (SAF). The results show that ROR has a positive and statistically significant impact on regional expenditure (coefficient 0.453308), meaning that increased local revenue directly leads to higher government spending. In contrast, GAF has a positive but statistically insignificant effect (coefficient 1.598782), indicating that higher central government transfers through GAF do not necessarily increase local government spending. Likewise, SAF shows a positive yet insignificant influence (coefficient 0.073499). Despite GAF and SAF not being individually significant, their combined effect with ROR on regional spending is statistically significant. The findings suggest evidence of a flypaper effect related to GAF, where central transfers have a greater impact on spending than local revenue, even though GAF individual effect is not significant. However, this effect is not observed with SAF. These findings emphasize the importance of enhancing local fiscal capacity to lessen dependence on central funding and encourage sustainable financial independence. The study recommends further research to explore additional factors influencing regional government expenditure.